Genomic and Epidemiological Surveillance of Zika Virus in the Amazon Region - Giovanetti, Marta (2020)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Flavivírus. Rio de Janeiro, RJ, Brasil / Universidade Federal de Minas Gerais. ICB. Laboratório de Genética Celular e Molecular. Belo Horizonte, MG, Brasil.